Role of ligands in the formation, phase stabilization, structural and magnetic properties of alpha-Fe2O3 nanoparticles - Joshi, Satyawati S.; Patil, Prajakta R.; Nimase, Madhav S.; Bakare, P. P. (Journal of Nanoparticle Research, 2006)
The electrochemical synthesis of alpha Fe2O3 nanoparticles was performed using quaternary ammonium salts viz. TPAB, TBAB and TOAB in an organic medium by optimizing current density and molar concentration of the ligand. The role of ligands in the formation of alpha phase, structure and magnetic properties was investigated in details. The effect of increasing chain length on the particle size confirmed that as the chain length increases from propyl to octyl, the particle size decreases. X-ray diffraction spectra of as prepared samples and TEM analysis confirmed the amorphous nature of iron oxide. TEM showed beads of iron oxide joined together with a size distribution in the range of 6-30 nm. The Mossbauer studies also support this observation that for the lowest particle size, the line width is broader which successively reduces with increase in particle size. Iron oxide capped with TOAB indicated superparamagnetic nature at room temperature. The resultant internal magnetic field of 506 mm/s due to hyperfine splitting clearly established the formation of alpha-Fe2O3 The infrared spectroscopy and pH measurements revealed the binding of tetra alkyl ligand with iron oxide. The IR spectra and the increase in basicity of as prepared samples confirmed the formation of hydrated iron oxide. Above 800 degrees C the spectra indicated only iron oxide. Surface area obtained by BET method was 205 m(2)/g.
Keywords: Alkyl chain length; alpha-Fe2O3; Electrochemistry; magnetic properties; Nanoparticles; narrow size distribution

Investigations of CdS and Ag-CdS nanoparticles by X-ray photoelectron spectroscopy - Thakur, Priya; Joshi, Satyawati S.; Patil, K. R. (Applied Surface Science, 2010)
In the present report, CdS and Ag-CdS nanoparticles were synthesized using cysteine as a capping agent. Surface properties CdS and Ag-CdS nanoparticles were studied by X-ray photoelectron spectroscopy (XPS). XPS study of CdS nanoparticles was carried out as a function of pH and for a refluxed sample at pH 11.2. Effect of dopant concentration on surface properties of Ag-CdS nanoparticles was also studied for as prepared samples as well as for annealed sample at 2% doping. Effect of pH, dopant concentration, and effect of particle size on different sulfur species present in the system was studied. Features of Cd 3d, S 2p and Ag 3d core level have been discussed in detail. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Ag-CdS; CdS; Cysteine; XPS

Low temperature pH dependent synthesis of flower-like ZnO nanostructures with enhanced photocatalytic activity - Vaishampayan, Mukta V.; Mulla, Imtiaz S.; Joshi, Satyawati S. (Materials Research Bulletin, 2011)
In the present study we have synthesized flower-like ZnO nanostructures comprising of nanobelts of 20 nm width by template and surfactant free low-temperature (4 degrees C) aqueous solution route. The ZnO nanostructures exhibit flower-like morphology, having crystalline hexagonal wurtzite structure with (001) orientation. The flowers with size between 600 and 700 nm consist of ZnO units having crystallite size of similar to 40 nm. Chemical and structural characterization reveals a significant role of precursor: ligand molar ratio, pH, and temperature in the formation of single-step flower-like ZnO at low temperature. Plausible growth mechanism for the formation of flower-like structure has been discussed in detail. Photoluminescence studies confirm formation of ZnO with the defects in crystal structure. The flower-like ZnO nanostructures exhibit enhanced photochemical degradation of methylene blue (MB) with the increased concentration of ligand, indicating attribution of structural features in the photocatalytic properties. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Catalytic properties; Defects; Nanostructures; Optical properties; Semiconductor

Optical and photocatalytic properties of single crystalline ZnO at the air-liquid interface by an aminolytic reaction - Vaishampayan, Mukta V.; Mulla, Imtiaz S.; Joshi, Satyawati S. (Langmuir, 2011)
Crystalline flowerlike ZnO was synthesized by an aminolytic reaction at the air-liquid interface in an aqueous media at an alkaline pH. A thin visible film was formed at the air-liquid interface by self-assembly of flowerlike ZnO. Diffraction studies show rearrangement of the single crystalline units at the air-liquid interface leading to the formation of nanobelts. These nanobelts overlap systematically to form petals of the flowerlike structure; individual petals get curved with time. Each nanobelt is found to be single crystalline and can be indexed as the hexagonal ZnO phase. The organic product formed in the aminolytic reaction and dissolution-reprecipitation mechanism is the driving force for the formation of flowerlike ZnO at the air-liquid interface. A clear relationship between the surface, photocatalytic, and photoluminescent properties of ZnO is observed. The flowerlike structure exhibits a blue shift (3.56 eV) in the band emission as compared to bulk ZnO (3.37 eV). The photodegradation of methylene blue over the flowerlike ZnO catalyst formed at the air-liquid interface and in the sediments shows enhanced photocatalytic activity. The sub-bands formed due to surface defects facilitate separation of charge carriers increasing their lifetime, leading to enhanced photocatalytic activity of flowerlike ZnO.